Entrepreneurship Education and Business Performance: Mediating Role of Innovation Capability and the Moderating Role of Policy Support in Tegal Raya - Elisa Dewiyanti; Elliot Simangunsong (Universitas Pendidikan Ganesha, 2026)
This study examines the effect of entrepreneurship education (EE) on the business performance (BP) of micro, small, and medium enterprises (MSMEs) in Tegal Raya, Indonesia, with innovation capability (IC) as a mediator and policy support (PS) as a moderator. Although prior studies have widely examined the effect of EE on entrepreneurial intention and start-up behaviour, limited empirical evidence explains how EE translates into actual MSME performance through innovation-related capability building within a supportive institutional environment. This study addresses that gap by integrating the Resource-Based View (RBV) and Institutional Theory in a moderated mediation model. A quantitative, cross-sectional design was employed, and data were collected from MSME owners who had participated in formal entrepreneurship education programmes. Of 350 returned questionnaires, 310 valid responses were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that EE has a positive and significant direct effect on BP (β = 0.39, p < 0.001) and a positive effect on IC (β = 0.51, p < 0.001), while IC also positively affects BP (β = 0.33, p < 0.01). In addition, IC significantly mediates the relationship between EE and BP (β = 0.17, p < 0.01), and PS positively moderates the relationship between EE and IC (β = 0.21, p < 0.05). These findings indicate that the impact of entrepreneurship education on MSME performance depends not only on educational content itself but also on the development of innovation capability and the presence of supportive policy conditions. The study contributes to the entrepreneurship and MSME literature by clarifying the internal and external mechanisms through which EE enhances firm performance in regional economies.